Book review: The apocryphal gospels within the context of early Christian theology - Toth, P (SAGE Publications, 2015)
Based on: The Apocryphal Gospels within the Context of Early Christian Theology, edited by Schröter J., Bibliotheca Ephemeridum Theologicarum Lovaniensium 260; Peeters 2013, Paperback; 90€; pp. xii+804, ISBN 978-90-429-2926-5